Designing A Talent Management Strategy To Address Organizational Transformation Challenges: A Case Study of PT. Sentosa Deli Mandiri - Wijaya, Doly Muhendy; Hartin Nst, Venny Fraya; Azaman, Azaman; Yuli Isnaini, Dewi Budhiartini (Universitas Ibn Khladun Bogor, 2025)
In today's business landscape, which is characterized by continuous technological change and increasingly fierce global competition, organizations are required to be able to adapt and transform effectively. Organizational transformation is not limited to operational changes, but also includes fundamental shifts in culture, structure, and overall organizational processes. The research question in this study focuses on how PT. Sentosa Deli Mandiri can design and implement effective talent management strategies to support the success of organizational transformation. The research methodology used is a case study approach, with data collection methods including in-depth interviews with top management and key employees, analysis of internal company documents, direct observation of work processes, and the distribution of questionnaires to employees to measure their perceptions of the talent management strategy that has been implemented. The research findings are expected to identify the main challenges faced by PT. Sentosa Deli Mandiri in the organizational transformation process, evaluate the effectiveness of existing talent management strategies, and formulate comprehensive and integrated talent management strategy recommendations aligned with the company's strategic business objectives.